ANALISIS CURRENT RATIO TERHADAP DEBT TO ASSET RATIO PADA PERUSAHAAN PROPERTY DAN REAL ESTATE - sofyan marwansyah (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2017)
Each company generally has the financial statements as a form of management of the operational activities for a specific period. After the financial statements are prepared based on the relevant data, and performed with the correct accounting procedures, it will show the condition of the company's financial statements sebenarnya.Agar more meaningful and understandable to stakeholders then need to do the financial analysis. Financial statement analysis is performed to measure and determine sajauh where the performance of a company at the moment. In this final project research is interested to analyze some of the commonly used ratio is the ratio of liquidity and solvency. This study aims to determine whether the liquidity ratio effect on solvency ratios simultaneously and partially. Independent variables used in this study is the current ratio (X) and the dependent variable is the debt to asset ratio (Y) .Rancangan research is hypothesis testing, with a sample of 20 property and real estate company listed on the Indonesia Stock Exchange year period 2010 to 2012. the data were processed using linear regression analysis using SPSS version 21. Based on the analysis performed on each - each variable, it can be concluded that the current ratio and debt to asset ratio has a relationship being and in the opposite direction to the value of R obtained by -0439. debt to asset ratio is influenced by the current ratio amounted to 19.2% the remaining 80.8% is influenced by other factors. regression line formed dalah Y = 0512-0042 X.